2017
DOI: 10.1002/mrc.4613
|View full text |Cite
|
Sign up to set email alerts
|

NMR study of phthalide‐type poly(phenylene)s. Symmetry and additivity

Abstract: All H and C NMR signals of the four poly(phenylenephthalides): polydiphenylenephthalide (P(DPh)-1), polyterphenylenephthalide (P(TPh)-2) and two sequentially ordered polymers with different ratios of alternating diphenylenephthalide and terphenylenephthalide units (P(DTPh)-3, P(DDTPh)-4) were assigned unequivocally with two-dimensional NMR techniques ( H- H COSY and NOESY; H- C HSQC and HMBC). There are four types of polyphenylene fragments: not symmetrical end, symmetrical inner, symmetrical pre-end and forma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…Chemical structures of C1-C4 polymers were confirmed using 1 H NMR, 13 C NMR and 19 F NMR spectra. Spectra for C1 and C3 were previously reported in [56], spectra for C4 were previously reported in [60].…”
Section: Polymer Nmr Characterizationmentioning
confidence: 99%
“…Chemical structures of C1-C4 polymers were confirmed using 1 H NMR, 13 C NMR and 19 F NMR spectra. Spectra for C1 and C3 were previously reported in [56], spectra for C4 were previously reported in [60].…”
Section: Polymer Nmr Characterizationmentioning
confidence: 99%
“…In a previous work, [ 13 ] studying the synthesis of polyarylenephthalides of the polyphenylene series using 13 C NMR spectroscopy, we found that aromatic fragments of the skeletal chain of the resulting polymers (diphenylene and terphenylene) can be separated by a symmetry plane passing through the center of the polyphenylene fragment into two halves, each of which is associated with the phthalide cycle adjacent to it. In turn, each phthalide cycle is associated with adjoining halves of two adjacent aromatic fragments.…”
Section: Introductionmentioning
confidence: 99%
“…A lot of physical and chemical properties of polycondensation copolymers, like all copolymers, in general, depend not only on their composition but also on the compositional heterogeneity (microheterogeneity), determined by the microstructure of macromolecules, which characterizes the distribution of monomer units along the polymer chain. The main method for studying the microstructure of polycondensation copolymers is high resolution NMR in its various modifications and, first of all, 1 H and 13 C NMR spectroscopy. The aliphatic-aromatic copolyesters obtained on the basis of iso-and terephthalic acids were studied in most detail by the 1 H NMR method.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations